(untitled) (Salam International Academic Journal, 2012)
The Causes of Change of Fatwa is a very important and sensitive topie. The author of this article has defined different juristic terms for clarification of the title of the article. He has sought, in its first part, to prove that Fatwa changes from time to time and has provided different reasons for this. In its second part, he has identified the factors requiring a change in Fatwa. These factors, seven according to him, are as following: Change in Ijtihad (interpretative judgment), change in custom, change in time, change in place, change in benefit/harm, change in cause, and change in status of the person seeking Fatwa.